2021
DOI: 10.1002/adma.202106079
|View full text |Cite
|
Sign up to set email alerts
|

2D Molecular Sheets of Hydrogen‐Bonded Organic Frameworks for Ultrastable Sodium‐Ion Storage

Abstract: little volume change during cycling. [15,16] It should be noted that albeit with high theoretic capacities, small organic molecules are often subjected to dissolution in the electrolyte at their charged or discharged states, and thereby suffer from very poor cyclability. [16] Poly merization through covalent bonding represents an effective strategy to suppress their dissolution. [17][18][19] A number of conjugated polymers (such as covalent organic frameworks or COFs) with different building units and topologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…The characteristic peaks located at 1597 cm −1 and 1392 cm −1 can be attributed to the asymmetric and symmetric stretches of the –COO– groups in the terephthalate ligand, 15 respectively. The peak of 2926 cm −1 can be ascribed to the O–H stretching vibration of N–H⋯O, and the peaks of 3068 cm −1 and 3248 cm −1 can be attributed to the N–H stretching vibration of N–H⋯N, 13 respectively, which indicates the existence of hydrogen bonding in the HOF material. In addition, the absorption peaks at 3200–3500 cm −1 can be attributed to the stretching vibration of the –OH group.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The characteristic peaks located at 1597 cm −1 and 1392 cm −1 can be attributed to the asymmetric and symmetric stretches of the –COO– groups in the terephthalate ligand, 15 respectively. The peak of 2926 cm −1 can be ascribed to the O–H stretching vibration of N–H⋯O, and the peaks of 3068 cm −1 and 3248 cm −1 can be attributed to the N–H stretching vibration of N–H⋯N, 13 respectively, which indicates the existence of hydrogen bonding in the HOF material. In addition, the absorption peaks at 3200–3500 cm −1 can be attributed to the stretching vibration of the –OH group.…”
mentioning
confidence: 97%
“…12 The diffraction peaks marked at 2 θ = 12.4°, 21.5°, 25.1°, and 29.2° are assigned to the HOF structure. 13 The wide-range X-ray photoelectron spectroscopy (XPS) survey spectrum (Fig. 2b) shows the presence of C, N, O, and Zr elements.…”
mentioning
confidence: 99%
“…Redox organic compounds are promising candidates as cathode materials for rechargeable batteries, by virtue of the advantages of renewable resources, low cost, and green synthesis with a low carbon footprint. Since the report of an organic cathode of dichloroisocyanuric acid in 1969, abundant redox compounds have been explored as organic electrode materials in various kinds of batteries. Among the reported organic electrodes, carbonyl compounds are some of the most competitive n-type cathode materials for SIBs, such as quinones, , imides, , and cyanuric acids, , due to the features of high theoretical capacities, high redox potentials, diverse structures, and extensive sources. , However, the high solubility of carbonyl compounds in organic electrolytes could result in a fast capacity decay during the cycling process, which is a showstopper hindering their practical applications. Increasing molecular weights by polymerization and introducing polar groups (e.g., COONa, SO 3 Na, aminotriazole) are two of the most adopted and universal strategies to tackle the dissolution issues of organic cathodes for SIBs. For instance, Tang et al reported a poly­(pentacenetetrone sulfide) (PPTS) cathode that could deliver a stable cycling performance of more than 10000 cycles with a capacity retention of 88%, while PPTS suffered a relatively poor rate capability possibly due to its nonconjugated and densely stacked polymer chains that might block the charges transfer . Wu et al introduced two aminotriazole polar groups into 1,4,5,8-naphthalenetetracarboxylic diimide (NTCDI) to synthesize a hydrogen-bonded organic framework (HOF-DAT), which achieved more than 10000 cycles with a capacity retention of 65%, since the formation of multiple hydrogen bonds between intramolecular aminotriazole groups reduced the solubility of HOF-DAT in most organic solvents .…”
mentioning
confidence: 99%
“…Among the reported organic electrodes, carbonyl compounds are some of the most competitive n-type cathode materials for SIBs, such as quinones, , imides, , and cyanuric acids, , due to the features of high theoretical capacities, high redox potentials, diverse structures, and extensive sources. , However, the high solubility of carbonyl compounds in organic electrolytes could result in a fast capacity decay during the cycling process, which is a showstopper hindering their practical applications. Increasing molecular weights by polymerization and introducing polar groups (e.g., COONa, SO 3 Na, aminotriazole) are two of the most adopted and universal strategies to tackle the dissolution issues of organic cathodes for SIBs. For instance, Tang et al reported a poly­(pentacenetetrone sulfide) (PPTS) cathode that could deliver a stable cycling performance of more than 10000 cycles with a capacity retention of 88%, while PPTS suffered a relatively poor rate capability possibly due to its nonconjugated and densely stacked polymer chains that might block the charges transfer . Wu et al introduced two aminotriazole polar groups into 1,4,5,8-naphthalenetetracarboxylic diimide (NTCDI) to synthesize a hydrogen-bonded organic framework (HOF-DAT), which achieved more than 10000 cycles with a capacity retention of 65%, since the formation of multiple hydrogen bonds between intramolecular aminotriazole groups reduced the solubility of HOF-DAT in most organic solvents . Wang et al observed that the introduction of sodium carboxylate could also effectively restrict the dissolution of NTCDI in a diethylene glycol dimethyl ether based electrolyte, which enabled the resulting disodium salt of N , N ′-bis­(glycinyl) naphthalene diimide (Na 2 BNDI) to show a capacity retention of 57.3% after 70000 cycles .…”
mentioning
confidence: 99%
See 1 more Smart Citation